Beyond romance fieldwork in Sarawak - Egay, Kelvin; Hew, Cheng Sim (Strategic Information and Research Development Centre, 2018)
A collection of experiences of anthropologists, historians and sociologists recounting the joys and frustrations of actually carrying out the necessary field work on which their academic work is based. The contributors are both from Malaysia and elsewhere their subjects are not only the indigenous peoples of the state, but other communities as well.